Piezo-driven thermoacoustic refrigerators with dynamic magnifiers - Nouh, M.; Aldraihem, O.; Baz, A. (Applied acoustics, 2014)
Thermoacoustic refrigeration is an emerging cooling technology which does not rely for in its operation on the use of any moving parts or harmful refrigerants. This technology uses acoustic waves to pump heat across a temperature gradient. The temperature gradient forms across the ends of a porous body, called the stack, enclosed in a resonator. The vast majority of thermoacoustic refrigerators to date have used electromagnetic loudspeakers to generate the acoustic input. In this paper, the design, construction, operation, and modeling of a piezo-driven thermoacoustic refrigerator are detailed. The performance of the refrigerator is significantly enhanced by coupling the acoustic driver with an elastic structure, referred to as a dynamic magnifier. Proper selection of the magnifier parameters can increase the magnitude of the pressure oscillations across the stack, and consequently the temperature difference. The magnified refrigerator demonstrates the effectiveness of piezoelectric actuation in moving 0.3W of heat across a 10°C temperature difference with an input power of 7W. All the theoretical predictions are validated against data from experimental prototypes. The developed theoretical and experimental tools can serve as invaluable means for the design and testing of piezo-driven thermoacoustic refrigerator configurations.